PERANCANGAN DATA WAREHOUSE DAN PENERAPAN DATA MINING UNTUK MENDUKUNG SISTEM INFORMASI AKADEMIK UNIVERSITAS KUNINGAN - Aah Sumiah; Dede Irawan; Fauziah . (NUANSA INFORMATIKA, 2013)
Good quality education is a goal to be achieved by any educational institution. In the world of education dynamically evolving the required educational institutions to improve the quality of education and graduates. To achieve this goal each competing institution to produce a model of innovation and education. Institutions can utilize the availability of appropriate information very influential in increasing the quality of service to students and help produce the right business decisions. The purpose of this study was to produce a model of the data warehouse Brass University Academic Information Systems and generate patterns of data mining to the data admission to prospective students determine possible re-register or not so if the resignation of incoming freshmen are expected to be known early will help the management campus to take the actions necessary to maintain the prospective student. This Tstudy used two models that modeling techniques for data warehouse star schema model and decision treeÂ  classification technique for data mining. Keyword: Data warehouse, data mining, classification, and decision tree